When prime brokers fail : the unheeded risk to hedge funds, banks, and the financial industry - Aikman, J. S. [ (Jonathan S.)] (Bloomberg Press/Wiley, 2010)
"When Prime Brokers Fail is a detailed look at the relationship between hedge funds and their brokerages and the risks that multiply in extraordinary markets. This relationship has been the source of unexpected risk for banks lending to highly leveraged hedge funds, as well as for the funds with assets at struggling banks"--Provided by publisher